PENGARUH MOTIVASI DAN KEAKTIFAN BELAJAR DALAM KELAS TERHADAP PRESTASI BELAJAR PENGGUNAAN ALAT UKUR - Riduan Riduan; Samidjo Samidjo (Jurnal Taman Vokasi, 2016)
The objectives of this study are to describe; (1) the influence of  learning motivation on learning achievement of measuring tool subject  (2) the influence of  learning activeness in class on learning achievement of measuring tool subject; and (3) the influence of  learning motivation  and learning activeness in class on learning achievement of measuring tool subject . This results of the study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used multiple regression. The study show that (1) there is positive and significant correlation between learning motivation with learning achievement of measuring tool subject; (2) there is  positive and significant correlation between learning activeness in class with learning achievement of measuring tool subject; and (3) there is positive and significant correlation between learning motivation and learning activeness in class with learning achievement of measuring tool subject.